2007
DOI: 10.1152/ajpregu.00888.2006
|View full text |Cite
|
Sign up to set email alerts
|

AMP does not induce torpor

Abstract: Swoap SJ, Rathvon M, Gutilla M. AMP does not induce torpor. Am J Physiol Regul Integr Comp Physiol 293: R468-R473, 2007. First published April 4, 2007; doi:10.1152/ajpregu.00888.2006.-Torpor, a state characterized by a well-orchestrated reduction of metabolic rate and body temperature (Tb), is employed for energetic savings by organisms throughout the animal kingdom. The nucleotide AMP has recently been purported to be a primary regulator of torpor in mice, as circulating AMP is elevated in the fasted state, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 43 publications
3
68
2
Order By: Relevance
“…adenosine monophosphate (Swoap et al 2006), H 2 S (Blackstone et al 2005) and 2-deoxy-D-glucose (Freinkel et al 1972)). Whether these responses are functionally similar to natural torpor has remained unclear (Swoap et al 2006), in part because manipulations such as fasting entail a non-trivial risk of death (Hudson & Scott 1979).…”
Section: Introductionmentioning
confidence: 99%
“…adenosine monophosphate (Swoap et al 2006), H 2 S (Blackstone et al 2005) and 2-deoxy-D-glucose (Freinkel et al 1972)). Whether these responses are functionally similar to natural torpor has remained unclear (Swoap et al 2006), in part because manipulations such as fasting entail a non-trivial risk of death (Hudson & Scott 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal injections of 5'-AMP have been shown to induce an artificial hypometabolic state in mice and rats as evidenced by a profound drop in Tb (Figure 8) [61,[76][77][78]. The putative contention is that intraperitoneal administration of high 5'-AMP concentrations (e.g., 500 mg/kg) lead to extensive 5'-AMP uptake by erythrocytes [79], after which the high intracellular levels of 5'-AMP drive the adenylate equilibrium (ATP + AMP  2 ADP) towards production of ADP, thereby depleting erythrocyte ATP levels [76,77].…”
Section: Adenosine Monophosphatementioning
confidence: 99%
“…As a result, erythrocyte 2,3-disphosphoglycerate is upregulated, limiting the binding of oxygen to hemoglobin's oxygen binding sites (referred to as oxygen affinity hypoxia) [76]. In addition to the already impaired oxygen transport, the severe cardiovascular depression following 5'-AMP administration has the potential to further exacerbate this hypoxic state (referred to as circulatory hypoxia) [78]. Although there is no conclusive evidence that these types of hypoxia have the ability to induce an anapyrexic state, the generally pervasive hypoxic state likely uses the S-Ztn-Tb(-Ta)-Q relationship ( Figure 6A) to induce hypometabolism through CB signaling.…”
Section: Adenosine Monophosphatementioning
confidence: 99%
“…Through one or more steps of dephosphorylation, ATP can be sequentially degraded to adenosine diphosphate (ADP), adenosine monophosphate (AMP), and adenosine. It has long been observed that adenosine induces hypothermia in a dose-dependent manner in mice [118][119][120]. Furthermore, the adenosine A1 receptor may play a key role because A1 receptor agonists other than adenosine also induce hypothermia [120,121].…”
Section: Adenosine and Adenine Nucleotidesmentioning
confidence: 99%
“…Some side effects of hypothermic drugs are quite common, such as reduction in mobility, cardiovascular function and decreased metabolism, as they are part of the hypothermic mechanisms [15,55,84,119,126]. In extreme cases, however, the side effects are so severe that their detrimental effects on ischemia outweigh the protective effects of the hypothermia [126], precluding their use against stroke.…”
Section: Summary and Considerationsmentioning
confidence: 99%